Answer:
The answer of your question is: y = - x + 11
Explanation:
Data
A (3, 8)
B (9,2)
Formula
m =
![((y2 - y1))/((x2 - x1))](https://img.qammunity.org/2020/formulas/mathematics/high-school/f6td1uulrkylnd63apxy7bdaoypgqj0hhf.png)
(y - y1) = m(x - x1)
Process
1.- Calculate the slope
m =
=
![(-6)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nweadq9ugdojqnek0prwqx7m4zwyxg9vwk.png)
m = -1 slope
2.- Substite point A and slope in the equation
(y - 2) = - 1(x - 9)
y - 2 = -x + 9
y = -x + 9 + 2
y = - x + 11 Solve for y